Algorithm for Selecting a Base Tractor Model to Form a Tractor Train - M. T. Toshboltaev; B. A. Kholikov (Сельскохозяйственные машины и технологии, 2019)
The main quality indicators of tractor trains (the number of trailers and their total load capacity, speed and stability of movement, braking distance, etc.) depends largely on the correct choice of the type of a base tractor. The existing methodological principles for optimizing the dimension range of agricultural tractors do not take into account the type of trailers. Therefore, the task of a rational choice of the base tractor type, taking into account the most complete utilization of the capacity of existing trailers and engine power, has become rather relevant. (Research purpose) Selection of a tractor model for hitching a group of 2PTS-4-793-03A two-axle trailers according to the criteria for carrying capacity and energy consumption of a tractor train. (Materials and methods) The authors have studied mass, weight and velocity parameters of the 2PTS-4-793-03A two-axle trailers, as well as the parameters characterizing the mechanical capabilities of the studied tractor. The studies employed the methods of implement mounting on machine-tractor units and elements of the theory of a tractor. (Results and discussion) The authors offer an algorithm of solving a problem of choosing a tractor. As a results, the ТТZ 60.10 tractor with a wheel formula of 4К2 available at farm enterprises and included in machine-and-tractor fleets and clusters has been selected as a power base of a tractor train. The authors have determined the number of trailers, which equals four, the tractor train speed ranges of 4-28 kilometers per hour, the tractor engine power amounting to 8.5-59.5 kilowatts, changes in critical values of the effective engine power corresponding to 13.492-94.444 kilowatts, as well as specified some other criteria. (Conclusions) The ТТZ 60.10 tractor with a wheel formula 4К2 and 46.7 kilowatt of effective engine capacity has been considered the optimal choice. It has been proved that this tractor can move four 2PTS-4-793-03A two-axle trailers with a total weight of 15,600 kilograms along asphalt-concrete roads with a rational speed of 9.505 kilometers per hour. The rationality of choice has been proved by calculating energy saving criteria: full traction efficiency accounts for 60 percent, engine load factor is 89 percent, and traction power utilization amounts to 96 percent.